Evaluating public programs : the impact of general revenue sharing on municipal government - Larkey, Patrick D., 1943- (Princeton legacy library., 1979)
For effective program evaluation, it is necessary to specify a counterfactual state, i.e., what would have happened without the program. Conventional approaches to program evaluation, preoccupied with technical and value issues, fail to address directly the need for counterfactual arguments. They also fail to recognize the indispensable role of positive theories of technical and behavioral processes in making these arguments. In order to understand the impact of the General Revenue Sharing (GRS) program on the fiscal behavior of municipal governments, Patrick Larkey develops and demonstrates an unconventional approach to program evaluation that overcomes these failures.Drawing on the positive theories of budgetary decisionmaking processes as well as longitudinal revenue and expenditure data from primary sources, the author specifies, estimates, and tests four "bureaucratic process" models for each of five city governments receiving GRS funds. Using these models to generate complex, counterfactual hypotheses, he then compares the counterfactual patterns with observed patterns to understand the fiscal effects of GRS.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.